Relasi Antar Disiplin Ilmu: Paradigma Integrasi dan Interkoneksi (Transdisiplinaritas) Ilmu Pengetahuan dengan Pendidikan Islam - Marzuki, Marzuki; Ghifari, Ahmad; Dirman, Dirman (Institut Agama Islam Negeri Kendari, 2023)
This study discusses the importance of integrating and interconnecting various disciplines in education, particularly through a transdisciplinary approach in the context of Islamic education, termed